ADAM23 in Cardiomyocyte Inhibits Cardiac Hypertrophy by Targeting FAK‐AKT Signaling. Issue 18 (18th September 2018) - Xiang, Mei; Luo, Hongbo; Wu, Jia; Ren, Lingyun; Ding, Xiangchao; Wu, Chuangyan; Chen, Jiuling; Chen, Shanshan; Zhang, Hao; Yu, Lu; Zou, Yanqiang; Xu, Heng; et al.
Abstract : Background: Cardiac hypertrophy has been recognized as an important independent risk factor for the development of heart failure and increases the risk of cardiac morbidity and mortality. A disintegrin and metalloprotease 23 (ADAM23), a member of ADAM family, is involved in cancer and neuronal differentiation. Although ADAM23 is expressed in the heart, the role of ADAM23 in the heart and in cardiac diseases remains unknown. Methods and Results: We observed that ADAM23 expression is decreased in both failing human hearts and hypertrophic mice hearts. Cardiac‐specific conditional ADAM23‐knockout mice significantly exhibited exacerbated cardiac hypertrophy, fibrosis, and dysfunction, whereas transgenic mice overexpressing ADAM23 in the heart exhibited reduced cardiac hypertrophy in response to pressure overload. Consistent results were also observed in angiotensin II‐induced neonatal rat cardiomyocyte hypertrophy. Mechanistically, ADAM23 exerts anti‐hypertrophic effects by specifically targeting the focal adhesion kinase‐protein kinase B (FAK‐AKT) signaling cascade. Focal adhesion kinase inactivation by inhibitor (PF‐562271) greatly reversed the detrimental effects in ADAM23‐knockout mice subjected to aortic banding. Conclusion: Altogether, we identified ADAM23 as a negative regulator of cardiac hypertrophy through inhibiting focal adhesion kinase‐protein kinase B signaling pathway, which could be a promising therapeutic target for this malady.